The Use and Effectiveness of Macroprudential Policies : New Evidence - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2015)
Using a recent IMF survey and expanding on previous studies, we document the use of macroprudential policies for 119 countries over the 2000-13 period, covering many instruments. Emerging economies use macroprudential policies most frequently, especially foreign exchange related ones, while advanced countries use borrower-based policies more. Usage is generally associated with lower growth in credit, notably in household credit. Effects are less in financially more developed and open economies, however, and usage comes with greater cross-border borrowing, suggesting some avoidance. And while macroprudential policies can help manage financial cycles, they work less well in busts.